A Systematic Approach to Achieving High Performance Hybrid Lighting Phosphors with Excellent Thermal‐ and Photostability. (7th December 2016) - Fang, Yang; Liu, Wei; Teat, Simon J.; Dey, Gangotri; Shen, Zeqing; An, Litao; Yu, Dechao; Wang, Lu; O'Carroll, Deirdre M.; Li, Jing
Abstract : The authors have designed and synthesized a family of high‐performance inorganic–organic hybrid phosphor materials composed of extended and robust networks of one, two, and three dimensions. Following a bottom‐up solution‐based synthetic approach, these structures are constructed by connecting highly emissive Cu4 I4 cubic clusters via carefully selected ligands that form strong CuN bonds. They emit intensive yellow‐orange light with high luminescence quantum efficiency, coupled with large Stokes shift, which greatly reduces self‐absorption. They also demonstrate exceptionally high framework‐ and photostability, comparable to those of commercial phosphors. The high stabilities are the result of significantly enhanced CuN bonds, as confirmed by the density functional theory (DFT) binding energy and electron density calculations. Possible emission mechanisms are analyzed based on the results of theoretical calculations and optical experiments. Two‐component white phosphors obtained by blending blue and yellow emitters reach an internal quantum yield as high as 82% and correlated color temperature as low as 2534 K. The performance level of this subfamily exceeds all other types of Cu–I based hybrid systems. The combined advantages make them excellent candidates as alternative rare‐earth element‐free phosphors for possible use in energy‐efficient lighting devices. Abstract : A precursor‐based and systematic bottom‐up synthesis approach has led to the development of a family of Cu4 I4 cubane‐based hybrid phosphor materials of 1D, 2D, and 3D extended networks with exceptionally high luminescence quantum efficiency, thermal‐ and photostability.